The reality of sports marketing from the point of view of administrators of sports institutions - علي ديب, خلود; خيربك, غنى أديب (Latakia University Journal -Medical Sciences Series, 2021)
The main objective of this research is to identify the reality of marketing in sports institutions from the point of view of employees and to identify the factors faced by sports institutions as well as highlighting the relationship between factors and methods in sports institutions, and to develop a proposed perception of the process of sports marketing, and to determine this, the study was conducted on a sample estimated at (50) Administrative in sports clubs, the researcher relied on the descriptive survey approach, where data was collected through designing a questionnaire to measure the level of use of marketing methods and to identify the most important obstacles that stand in the way of sports marketing in sports institutions. The results resulted in a weakness in the exploitation of marketing methods by sports federations, especially licensing the use of signs and logos on products, and that there is a lack of specialized committees in the field of sports marketing working to achieve the goals of the institution and achieve the required income, and that there is a shortage of specialists in marketing sports activities, especially the absence of a department responsible for marketing, and that the current laws are not in line with marketing policies, that the financial income from marketing in sports clubs has not reached the stage of satisfaction.